Artificial intelligence in athletics coaching: Barriers, constraints, and practical challenges - Sukkarieh, Rawa'ah; Al-Nahar, Hazem Nouri; Abu A’Aqoulah, Karam Abu; Alshadideh, Maysaloun Kamel; Alshaer, Ayat; Al-Dhmour, Maryam Majed; Al-Jarrah, Shefa' Salah (Research Journal in Advanced Humanities, 2026)
This study aimed to identify the Challenges facing athletics coaches in applying artificial intelligence techniques, the researchers used the descriptive method in his survey method due to its suitability and the nature of the study, the study sample consisted of (364) athletics coaches from the directorates of education of the Jordanian Ministry of Education, and to address the analytical aspects of the subject of the study, the researchers turned to collecting raw data by building a questionnaire for the Challenges facing athletics coaches in the application of artificial intelligence techniques, which consists of (28) paragraphs distributed over three axes ( the cognitive axis (8) paragraphs, the technical axis: (10) paragraphs, and the organisational axis (10) paragraphs. The researchers used the following statistical methods (arithmetic mean, standard deviation, Cronbach's alpha coefficient to measure internal consistency, and Pearson correlation coefficient. As for the technical Challenges, "the two institutions do not have the necessary technical infrastructure to use artificial intelligence technologies when training for athletics", while the organizational Challenges were "there are not enough financial resources for the use of artificial intelligence systems", and the study recommended many recommendations, the most important of which are: equipping the various institutions concerned with athletics with a modern infrastructure for the use of artificial intelligence systems.